MENINGKATKAN KREATIVITAS MATEMATIKA MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING DAN DAMPAKNYA TERHADAP SIKAP SERTA HASIL BELAJAR - Heri Herwanto (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2016)
The study, entitled "Enhancing Creativity Learning Mathematics through Project Based Learning Model and Its Impact on Attitude and Learning Outcomes" conducted on students of the second semester study program Information Systems Faculty of Computer Science University of Brass. This research is motivated by the fact that the survey results indicate a lack of creativity of mathematics, consequently affect the poor attitude and mathematics learning outcomes. The study aims to analyze whether there was an effect Implementation Project Based Learning Model Learning to creativity, attitude and student results. The research method used mixmethode, where quantitative data and qualitative data presented to strengthen each other and interpreted based on the facts and findings that occurred during the study. Based on the research results obtained by the fact that the amount of influence the implementation of Project Based Learning Model Learning for Creativity, Attitude and Learning Outcomes are sinifikan. improvement of learning outcomes based on the value of the gain shows the medium category, and the response to the application of the Model Student Learning Project Based Learning is positive. Based on the findings, with the implementation of Project Learning Model Based Learning, students gain learning experience complete and intact because it is done step by step based on the concepts of mathematics to produce a project that could be used for community needs.Keywords: Learning Model Project Based Learning, Creativity, Attitudes, Learning Outcomes